Investigation on the mechanical properties and microstructure analysis of micro-resistance spot welding between stainless steel 316L and Tl-6AL-4V / Muhammad Safwan Mohd Mansor - Muhammad Safwan, Mohd Mansor (2020)
In this study, ASS 316L and Ti-6Al-4V were welded together by micro-resistance spot welding (μRSW) at different combinations of welding parameters using specifically design electrode geometry in order to acquire the optimal combination of welding parameters. The welded joint were subjected to tensile shear strength test to determine the influence of welding current, welding time, welding force and different design of elctrode tip on the mechanical properties and the strength of the welded joint. The experiment was conducted by using full factorial design of experiment (DoE) with L27 orthogonal array and utilizing the analysis of variance (ANOVA) to obtain the most significant welding parameter which affect the strength of the welded joint. In addition, micro hardness and microstructural examinations of the fracture mode (failure analysis) were carried out. The results revealed that by using combination of 2.0 kA welding current, 100 ms welding time and 241 N welding force yield the highest load value, 378.25 N. Welding current found to be the most significant welding parameter. Vickers microhardness test reveal an average hardness value of 963 HV at the fusion zone (FZ). After the optimal parameters have been obtained, an investigation has been carried out to obtain the suitable design of electrode geometries by implementing three different design of electrode tip, triangle, square and hexagon shape through comparison study. The comparison study involves the joint strength and microhardness evaluation. Based on the SEM observations, dendritic grain structures can be seen at the FZ. In addition, EDS mapping analysis revealed the formation of Ti-Fe and Ti-Fe2 intermetallic compound at the FZ. This is further supported by results obtained by vickers microhardness test as hardness value (HV) at the FZ is significantly higher than the base metals. Lastly, the overall results reveal that pimpled tipped (PT) electrode with triangle shape electrode tip shows superior welded joint strength.